Prospective clinical study of bilateral balanced occlusion (BBO) versus canine-guided occlusion (CGO) in complete denture wearers - Brandt, Silvia; Danielczak, Regina A. (Clinical oral investigations, 2019)
Objectives: Previous studies have often discussed occlusal concepts for complete dentures without formulating a recommendation. Various options are available, the most common ones being canine-guided occlusion (CGO) and bilateral balanced occlusion (BBO). We designed a prospective randomized study to compare these two schemes with the goal of formulating a recommendation. Materials and methods: Forty patients could be evaluated. In a crossover design, they were randomized to a CGO>BBO group and a BBO>CGO group, each starting out by wearing their dentures with the first occlusal scheme for 3 months, followed by a first investigator- and patient-centered assessment. Then, each patient was transitioned to the other occlusal scheme by replacing the denture setup in the dental laboratory, followed by another 3 months of intraoral use and a second assessment. Wilcoxon-Mann-Whitney and marginal homogeneity tests were used for statistical analysis. Results: All statistically significant differences favored the CGO concept. Based on patient ratings, the CGO>BBO group preferred its esthetics (p = 0.02) and the BBO>CGO group its mandibular retention (p = 0.05), phonetics (p = 0.03), and masticatory function (p = 0.01). Based on investigator assessments, maxillary denture retention was found to significantly improve among the BBO>CGO patients after transition to CGO (p = 0.01). Conclusions: Within the limitations of this study, canine guidance can be recommended as a comfortable alternative to bilateral balanced occlusion for complete dentures.Clinical relevanceThis recommendation can reduce the time requirements for the fabrication of complete dentures in dental laboratories.